A quiet flame : a Bernie Gunther novel - Kerr, Philip (Kerr, Philip. Bernie Gunther novel., 2009)
Buenos Aires, 1950. After being falsely accused of war crimes, Bernie Gunther<U+2014>like the Nazis he has always despised<U+2014>has been offered a new life and a clean passport by the Perón government. But the tough, fast-talking ex-Berlin detective doesn<U+2019>t have the luxury of laying low. The local police pressure Bernie into taking on a case in which a girl has turned up gruesomely mutilated. What<U+2019>s more, her murder just might be linked to a missing German banker<U+2019>s daughter and a long-unsolved case Bernie worked back in Berlin before the war. After all, the scum of the earth has been washing up on Argentina<U+2019>s shores<U+2014>state-licensed murderers and torturers<U+2014>so why couldn<U+2019>t a serial killer be among them?